Fixing with intramedullary nails in femor fracture in ant eater, Myrmecophaga Tridactyla-Linnaeus, 1758. Case report - Bonnon, Melody; Oliveira e Souza, Lucio de; Ortunho, Vanessa Veronese (Univ Federal Ceara, Centro Ciencias Agrarias, 2015)
An ant eater male 30 kg was found on a highway at Ilha Solteira-SP, and were taken to Wild Conservation Center (WCC), where he was diagnosed with a simple oblique fracture in the diaphisi's femur, and a fracture in radio-ulna, both on the right side. The animal was subjected to surgical procedures for fixation of the femur. After the first fixation, the fracture was reduced with good alignment of the bone and rotation movements were completely absent. Two days after surgery was done X-rays, that showed that the intramedullary pin was moved, causing an unacceptable alignment of the bone. Were done a second surger to remov the pin and put other. Seven days after the second surgery, the wound showed signs of infection and the animal was anesthetized for further evaluation, and the intramedullary pin was found to have doubled again. Considering these signs, progressive weight loss of the animal and the aggressive nature, made the intensive care impossible without daily sedation, and from that, the option to euthanize the animal was the best choice. The post mortem evaluation confirmed the surgical site infection, although local and systemic antibiotic therapy.
Keywords: extern imobilization; treatment; wild animal